Menstrual, reproductive and hormonal factors and thyroid cancer: a hospital-based case–control study in China - Meng Wang; Wei-Wei Gong; Qing-Fang He; Ru-Ying Hu; Min Yu (BMC Women's Health, 2021)
Abstract Background There have been considerable studies on the effects of reproductive factors on thyroid cancer risk, while findings are inconsistent. In this analysis, we aimed to investigate the associations between menstrual, reproductive and hormonal factors with thyroid cancer occurrence in a population of Chinese women. Methods Using data from a 1:1 matched case–control study performed between 2015 and 2017 in Zhejiang Province of China, a second analysis of 2261 pairs of female subjects was conducted. The possible effects for thyroid cancer were evaluated in logistic regression models by odds ratios (ORs) with 95% confidence intervals (CIs). Results Later age at first pregnancy (for > 25 vs. ≦ 20 years, OR: 0.47, 95% CI 0.23–0.96) and longer duration of breast feeding (for 6–12 vs. ≦ 6 months, OR: 0.49, 95% CI 0.24–0.98) were significantly associated with decreased occurrence of thyroid cancer, while no trend was observed. Stratified by age at enrollment, only the association with duration of breast feeding remained significant, but limited to younger women (≦ 50 years). Conclusions Our results suggested that women with later age at first pregnancy or longer breast feeding duration were less likely to have thyroid cancer. These findings supported an influence role of reproductive factors in thyroid cancer risk.